The Computer Use Intention (CUI) scale in education development, validity and reliability studies - Kung Teck Wong, Mokhsein Siti Eshah, Swee Pauline, Choo Goh, Hanafi Hafizul, (N/A, 2013)
The Computer Use Intention (CUI) scale in education development, validity and reliability studies by Kung Teck Wong, Mokhsein Siti Eshah, Swee Pauline, Choo Goh, Hanafi Hafizul,